2022
DOI: 10.1016/j.ekir.2022.01.1055
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future of Phosphate Management

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Hypocalcemia increases PTH levels (secondary hyperparathyroidism), resulting in increased bone resorption of calcium, thereby causing soft tissue mineralization and bone de-mineralization. Aluminum- and calcium-based phosphate binders, sevelamer carbonate, and lanthanum carbonate are most frequently used for treating hyperphosphatemia [ 14 , 23 , 24 ]. In this clinical study, researchers aimed to compare the therapeutic and other vital parameter effects of aluminum- and calcium-free phosphate binder for six months in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocalcemia increases PTH levels (secondary hyperparathyroidism), resulting in increased bone resorption of calcium, thereby causing soft tissue mineralization and bone de-mineralization. Aluminum- and calcium-based phosphate binders, sevelamer carbonate, and lanthanum carbonate are most frequently used for treating hyperphosphatemia [ 14 , 23 , 24 ]. In this clinical study, researchers aimed to compare the therapeutic and other vital parameter effects of aluminum- and calcium-free phosphate binder for six months in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly aluminum- and calcium-free phosphate binders such as sevelamer carbonate and lanthanum carbonate are available on the market as treatment options for hyperphosphatemia. Both decrease serum phosphate levels and low-density lipoprotein (LDL) cholesterol and increase high-density lipoprotein (HDL) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLC34 transporters are also inhibited by EOS789 but at slightly higher concentrations. The properties of EOS789 indicate that it has therapeutic potential for hyperphosphatemia associated with chronic kidney disease ( Tsuboi et al, 2020 ; Hill Gallant et al, 2021 ; Doshi and Wish, 2022 ; Tsuboi et al, 2022 ). For a recent review of Na + -Pi cotransporter pharmacology, see Wagner, 2023 .…”
Section: Pi Influx: Mammalian Na + -Pi Cotransportersmentioning
confidence: 99%
“…Thus, it may directly contribute to vascular damage by pro-inflammatory actions on the vascular smooth muscle cell leading to endothelial dysfunction and promoting vascular calcification [ 23 , 24 ]. Furthermore, a high dietary phosphate content may contribute to atherogenesis [ 25 ] and has also been linked to a more rapid progression of CKD to ESKD [ 19 , 26 , 27 ]. Using data from the US Renal Data System, Block et al [ 4 ] found an increased risk of death (relative risk, 1.27) associated with serum phosphate levels > 6.5 mg/dL.…”
Section: Introductionmentioning
confidence: 99%